Effect of Preparation for Discharge Readiness Program on Readiness for Hospital Discharge among Older Patients Undergoing Orthopedic Surgery - Kudwongkaew, Chaowalit; Leethong-in, Mayuree (Journal of Phrapokklao Nursing College, Chanthaburi, 2025)
This quasi-experimental research aimed to investigate the effect of preparation for discharge readiness program on readiness for hospital discharge among older patients undergoing orthopedic surgery. The samples were 30 older patients undergoing orthopedic surgery admitted to Srinagarind Hospital. They were equally divided into an experimental group (n = 15) and a control group (n = 15). The research instruments consisted of the preparation for discharge readiness program among older patients undergoing orthopedic surgery, the Mini-cog, the 2 screening questions (2Q), the general information interview form, and the Readiness for Hospital Discharge Scale (RHDS)-Adult Form with a reliability of .79. The implementation and data collection were conducted from January to April 2023. Data were analyzed by frequency, percentage, mean, standard deviation, and independent t-test. The research results revealed that after the experiment, the experimental group had statistically significantly higher mean score of readiness for hospital discharge than the control group (t = 18.763, p < .001). This research suggests that nurses should adopt this preparation for discharge readiness program among older patients undergoing orthopedic surgery. This will help increase readiness for hospital discharge.